2023
DOI: 10.1002/ppap.202200233
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of oxazoline‐based plasma polymers for biosensing applications

Abstract: Plasma‐polymerized polyoxazoline (POx) thin films offer a fast, scalable, and solvent‐free method of electrode functionalization through the unique chemistry of the oxazoline ring. However, for POx to be a viable green alternative to existing surface modification approaches, the films should be able to withstand the processing steps involved in biosensing. Here, the effects that current exposure, extended incubation, and repeated electrode rinses have on the electrochemical and physical stability of polymethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The exposed electrode area for the measurements was 1.767 cm 2 . The CV tests were conducted in a custom-made single-cell setup with a Pt wire as a counter electrode and a Ag/AgCl reference electrode . All potentials reported were calibrated to a reversible hydrogen electrode (RHE) by E (RHE) = E (Ag/AgCl) + 0.195 V + 0.0591 × pH.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The exposed electrode area for the measurements was 1.767 cm 2 . The CV tests were conducted in a custom-made single-cell setup with a Pt wire as a counter electrode and a Ag/AgCl reference electrode . All potentials reported were calibrated to a reversible hydrogen electrode (RHE) by E (RHE) = E (Ag/AgCl) + 0.195 V + 0.0591 × pH.…”
Section: Methodsmentioning
confidence: 99%
“…The CV tests were conducted in a custom-made single-cell setup with a Pt wire as a counter electrode and a Ag/AgCl reference electrode. 41 All potentials reported were calibrated to a reversible hydrogen electrode (RHE) by E(RHE) = E(Ag/AgCl) + 0.195 V + 0.0591 × pH. Two sets of conditions were investigated: mild and harsh conditions.…”
Section: Atomic Force Microscopy and Scanning Electronmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Electrochemical investigations have shown that the intrinsic structure of the POx films significantly influences the charge transfer resistance of the coating independently of the film thickness. 8 Importantly, careful optimization of the deposition conditions was required to balance the POx films’ electrochemical performance and their stability to external processing, such as incubation steps, rinse cycles, and repeated current exposure.…”
Section: Introductionmentioning
confidence: 99%
“…POxs are promising platforms for drug delivery applications due to their biocompatibility and stealth properties [6]. Plasma-polymerized POx thin films from oxazoline precursors were investigated and optimized as an alternative approach for electrode functionalization for electrochemical immunosensors [7,8]. Currently, there are many applied studies related to the water solubility, invisibility and thermoresponsive of POxs.…”
Section: Introductionmentioning
confidence: 99%